Geometrical variations in solar stills for improving the fresh water yield—A review. Issue 45 (25th September 2016) - Sathyamurthy, Ravishankar; Harris Samuel, D.G.; Nagarajan, P.K.; Arunkumar, T.
Abstract: Water consumption by humanity is one of the major yardsticks to assess its civilization. Humans depend on groundwater sources for drinking. Some of these underground water sources cannot be used for drinking due to pollution. To solve the issues related to drinking water, several methods are employed, and a promising one is solar desalination. This paper communicates a review of different geometrical shapes of solar still. The present study concludes that the geometry in the solar still significantly influences the yield of fresh water.